2021
DOI: 10.1021/acs.est.1c05503
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal Activity and Nutrient Uptake from Wastewater Enhanced by Nanoscale Zerovalent Iron: Performance and Molecular Mechanism

Abstract: Microalgae-based bioremediation presents an alternative to traditional biological wastewater treatment. However, its efficiency is still challenging due to low microalgal activities and growth rate in wastewater. Iron plays an important role in microbial metabolism and is effective to stimulate microbial growth. In this study, a novel approach was proposed to simultaneously promote microalgal activity and nutrient uptake from wastewater using nanoscale zerovalent iron (nZVI), and the underlying molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 51 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…The SBR had been operated for over two years prior to experiments with stable nitrogen removal performance. The compositions of SMW shown in the SI Text1 . The LED light board used here had 80% similarity to solar irradiance to provide various light required in experiments (Kesheng Laboratory Instruments Co. LTD, NingBo, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SBR had been operated for over two years prior to experiments with stable nitrogen removal performance. The compositions of SMW shown in the SI Text1 . The LED light board used here had 80% similarity to solar irradiance to provide various light required in experiments (Kesheng Laboratory Instruments Co. LTD, NingBo, China).…”
Section: Methodsmentioning
confidence: 99%
“…The compositions of SMW shown in the SI Text1. 14 The LED light board used here had 80% similarity to solar irradiance to provide various light required in experiments (Kesheng Laboratory Instruments Co. LTD, NingBo, China).…”
Section: Seed Sludge and Lightmentioning
confidence: 99%
“…The shift from nutrient removal to resource recovery has been attracting increasing attention in the field of municipal wastewater (MW) treatment. Microalgal bioremediation is one of the promising alternatives to conventional technologies due to its competitive advantages such as nutrient recycling with simultaneous production of value-added biomass. However, its industrialization was largely limited by unstable microalgal activities in the MW treatment plant (MWTP), which experienced an abrupt change in nutrient loadings due to the fluctuations in both wastewater quality and quantity. Particularly, the periodic high-ammonium (NH 4 + -N) strength accompanied by the influent would lead to unsatisfactory microalgal growth and even the failure of the entire system. , …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one-sided explanations were reported that FA might suppress microalgal photochemical activities by destroying the oxygen-evolving complex (OEC) (through uncoupling the Mn cluster) and disordering non-photochemical quenching (through disturbing the internal pH of the thylakoid lumen). , Other metabolic activities (e.g., nutrient recycling) and multiple physiological resistances (e.g., antioxidant system and photoprotection process) were rarely investigated. For instance, photoprotection pathways [e.g., cyclic electron transport (CET) and decreased light harvesting] have been identified to ensure the continuation of photosynthetic activities. , All these metabolic and physiological responses to FA shock require further investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation